2014
DOI: 10.1002/hep.27283
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality on the liver transplant waiting list: Unintended policy consequences and model for End‐Stage Liver Disease (MELD) inflation

Abstract: The Model for End-Stage Liver Disease (MELD) allocation system for liver transplantation provides "exceptions" for diseases such as hepatocellular carcinoma (HCC). It was the aim of this study to assess equipoise between exception candidates and nonexception candidates on the waiting list and to assess if the exception system contributes to steadily increasing regional MELD at transplant. In all, 78,595 adult liver transplant candidates between January 2005 and December 2012 were analyzed. Yearly trends in wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
142
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 14 publications
(14 reference statements)
4
142
2
6
Order By: Relevance
“…Direct clinical implications of the organ shortage, like pre-LT rising transfusion need, prolonged waiting times and increasing MELD scores, have shown to promote the risk of immunologic imbalance [127,134,148] . This could be one explanation for the reported outcome deterioration in the MELD era [5,[10][11][12][13][14] . As a consequence, pre-LT immunologic screening has been recently recommended, particularly in high-risk liver patients [137,138,149] .…”
Section: Ivig and Lt With Positive T-lymphocytotoxic Crossmatchmentioning
confidence: 95%
See 1 more Smart Citation
“…Direct clinical implications of the organ shortage, like pre-LT rising transfusion need, prolonged waiting times and increasing MELD scores, have shown to promote the risk of immunologic imbalance [127,134,148] . This could be one explanation for the reported outcome deterioration in the MELD era [5,[10][11][12][13][14] . As a consequence, pre-LT immunologic screening has been recently recommended, particularly in high-risk liver patients [137,138,149] .…”
Section: Ivig and Lt With Positive T-lymphocytotoxic Crossmatchmentioning
confidence: 95%
“…As a result, donors' and recipients' selection criteria were considerably expanded and numbers of LTs performed were significantly increasing in recent years. Due to a dramatic donor organ shortage, growing waiting lists, prolonged waiting times and increasing pre-LT mortality rates have been reported [4][5][6] . To respond to this challenging situation, the model of end-stage liver disease (MELD) score was implemented to give priority to the most urgent patients on the waiting lists.…”
Section: Introductionmentioning
confidence: 99%
“…3 Interestingly, the American situation regarding patients enlisted to transplant with exceptions to the MELD-based system is quite similar to the Brazilian one, which can be exemplified by the percentage of enlisted patients with HCC, 19.00% in the American study 1 and 19.60% in the post-MELD era of the Brazilian study.…”
mentioning
confidence: 91%
“…This letter regards the interesting article published by Northup et al 1 The researchers demonstrated that, under the Model for End-Stage Liver Disease (MELD)-based allocation system for liver transplantation, patients with exceptions to this system, especially those with hepatocellular carcinoma (HCC), have a great advantage over nonexception candidates in waiting list mortality and in access to transplant, leading to inequity.…”
mentioning
confidence: 99%
See 1 more Smart Citation